Preparation method and application of iridium oxide / ferronickel hydroxide composite catalyst
The preparation of iridium oxide/nickel iron hydroxide composite catalysts through dielectric barrier discharge and hydrothermal method solves the problems of high production cost and complex process of hydrogen evolution catalysts, and achieves efficient and stable catalytic performance and low-cost production, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411400987.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The existing hydrogen evolution catalyst has high production costs, complex preparation process, insufficient catalytic efficiency and electrocatalytic stability, making it difficult to be suitable for industrial applications.
The metal iron foam with a three-dimensional skeleton structure is pretreated by plasma surface by dielectric barrier discharge, and the mixed solution of nickel nitrate, iridium oxide, urea and ammonium fluoride is immersed in a hydrothermal reaction to form iridium oxide/nickel iron hydrogen The oxide composite catalyst is supported on the three-dimensional mesh iron foam material by a one-step hydrothermal method.
It improves the hydrogen evolution activity and conductivity of the catalyst, reduces production costs, simplifies the process flow, and enhances the stability and commercial application value of the catalyst.
Smart Images

Figure CN119287427A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of an iridium oxide / nickel iron hydroxide composite catalyst. Background Art
[0002] As environmental pollution caused by the extensive use of traditional fossil fuels becomes increasingly serious, the research and development of renewable energy has become one of the key issues of public concern. Among various new energy technologies, the production of hydrogen and oxygen by electrolysis of water is regarded as a promising method for obtaining clean energy. However, due to the slow chemical conversion rate in this process, a large additional voltage is required to promote the reaction. Therefore, improving the efficiency of water electrolysis catalysts to reduce the required overpotential and reduce energy consumption has become a research focus. Although precious metals such as platinum (Pt) and ruthenium (Ru) perform well as catalysts, they are difficult to be widely used in industrial production due to their scarce resources, high cost and insufficient electrochemical stability. Therefore, it is particularly important to find non-precious metal-based catalysts that are efficient, economical and easy to mass produce. Transition metal phosphides have attracted widespread attention due to their unique electronic properties and reported high-efficiency electrocatalytic performance, but existing studies have also pointed out their shortcomings in production cost, preparation complexity, catalytic efficiency and electrocatalytic stability, as well as possible negative impacts on the environment.
[0003] The patent with publication number CN117089885A discloses an iridium-doped nickel-iron-oxide-based composite catalyst and its preparation method and application. The preparation method uses physical vapor deposition to prepare this composite catalyst on a polyhexabenzocoronene network material. The composite catalyst has a high specific surface area and good electrical conductivity and is suitable for oxygen evolution reaction. However, the catalyst is not applied to hydrogen evolution reaction, and the advantages of iridium-nickel-iron in hydrogen evolution application are not reflected. Moreover, its process flow is relatively complicated and costly, and it is not suitable for industrial application. The patent with publication number CN118256951A discloses an iridium single atom @ oxygen-rich vacancy nickel hydroxide nanosheet and its preparation method and application. The preparation method uses a pre-treated nickel foam in a mixed solution of chloroiridic acid and hydrochloric acid to form Ni 2+ , followed by hydrolysis to generate ultra-thin nickel hydroxide nanosheets containing rich oxygen vacancies, and iridium single atoms anchored on the surface of these nanosheets, and finally in situ growth of iridium single atoms @ oxygen vacancy-rich nickel hydroxide nanosheets on nickel foam; however, the preparation cost is high and the process is complicated, which is not suitable for large-scale application. Summary of the invention
[0004] The present invention aims to solve the technical problems of high production cost, complex preparation process, insufficient catalytic efficiency and electrocatalytic stability of existing hydrogen evolution catalysts, and provides a preparation method and application of an iridium oxide / nickel iron hydroxide composite catalyst.
[0005] The preparation method of the iridium oxide / nickel iron hydroxide composite catalyst of the present invention is carried out according to the following steps:
[0006] 1. Plasma surface pretreatment of metallic iron foam with three-dimensional skeleton structure using dielectric barrier discharge;
[0007] 2. adding the metallic iron foam after the plasma pretreatment in step 1 into a mixed aqueous solution of nickel nitrate, iridium oxide, urea and ammonium fluoride to completely immerse it, and then subjecting it to a hydrothermal reaction. After the reaction is completed, the iridium oxide / nickel iron hydroxide composite catalyst is obtained by washing and drying in sequence;
[0008] The mass ratio of the nickel nitrate, iridium oxide, urea and ammonium fluoride is (8-9):(5-6):(30-32):(9-10);
[0009] The temperature of the hydrothermal reaction is 120°C to 140°C.
[0010] The iridium oxide / nickel iron hydroxide composite catalyst prepared by the invention exhibits excellent electrocatalytic performance and is applied as a catalyst in a hydrogen evolution reaction.
[0011] The introduction of iridium oxide in the present invention greatly improves the hydrogen evolution kinetics of nickel-iron hydroxide, while the in-situ growth of the catalyst and the electronic regulation of iridium enhance the conductivity of the catalyst and promote electron transfer, thus greatly improving the hydrogen evolution activity of the prepared iridium oxide / nickel-iron hydroxide composite catalyst.
[0012] The preparation method of the present invention can ensure that the catalyst (iridium oxide / nickel iron hydroxide composite material) is evenly distributed and firmly attached to the base metal iron foam in the hydrothermal synthesis step, thereby forming a material with good stability. Compared with the traditional preparation process, this method enhances the conductivity and surface active area of the base through the pretreatment stage, thereby improving the overall performance of the catalyst, reducing the production cost, and enhancing the durability of the electrode material, opening up new possibilities for industrial production and practical applications.
[0013] The beneficial effects of the present invention are:
[0014] (1) The present invention adopts a one-step hydrothermal method to load an iridium oxide / nickel iron hydroxide composite catalyst on a three-dimensional network iron foam material. The prepared iridium oxide / nickel iron hydroxide composite catalyst has good hydrogen evolution performance and good electrical conductivity, has a good catalytic effect when used for oxygen evolution reaction, and has strong catalytic stability;
[0015] (2) The iridium oxide / nickel iron hydroxide composite catalyst prepared by the present invention has a very small amount of iridium doping, which can greatly reduce the amount of precious metals used and has a good catalytic effect, low manufacturing cost, and high commercial application value;
[0016] (3) The preparation method of the present invention is simple in process and easy to operate, and provides a new idea for the new oxygen evolution reaction catalyst to continue to pursue the goal of high activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the XRD pattern of the iridium oxide / nickel iron hydroxide composite catalyst prepared in Experiment 1;
[0018] Figure 2 This is a high-magnification SEM image of the iridium oxide / nickel iron hydroxide composite catalyst prepared in Experiment 1;
[0019] Figure 3 This is a low-magnification SEM image of the iridium oxide / nickel iron hydroxide composite catalyst prepared in Experiment 1;
[0020] Figure 4 is the hydrogen evolution polarization curve in Experiment 2;
[0021] Figure 5 This is the hydrogen evolution polarization curve in Experiment 3. DETAILED DESCRIPTION
[0022] Specific implementation method 1: This implementation method is a method for preparing an iridium oxide / nickel iron hydroxide composite catalyst, which is specifically carried out according to the following steps:
[0023] 1. Plasma surface pretreatment of metallic iron foam with three-dimensional skeleton structure using dielectric barrier discharge;
[0024] 2. adding the metallic iron foam after the plasma pretreatment in step 1 into a mixed aqueous solution of nickel nitrate, iridium oxide, urea and ammonium fluoride to completely immerse it, and then subjecting it to a hydrothermal reaction. After the reaction is completed, the iridium oxide / nickel iron hydroxide composite catalyst is obtained by washing and drying in sequence;
[0025] The mass ratio of the nickel nitrate, iridium oxide, urea and ammonium fluoride is (8-9):(5-6):(30-32):(9-10);
[0026] The temperature of the hydrothermal reaction is 120°C to 140°C.
[0027] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the power of the dielectric barrier discharge in step 1 is 50W to 100W. The rest is the same as specific implementation method 1.
[0028] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the dielectric barrier discharge time in step 1 is 8 minutes to 12 minutes. The rest is the same as specific implementation method 1 or 2.
[0029] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: in step 1, before pretreatment, the metal iron foam with a three-dimensional skeleton structure needs to be immersed in acetone for ultrasonic cleaning, and then washed with anhydrous ethanol and deionized water for multiple times, and then placed in a vacuum drying oven for drying. The rest is the same as specific embodiments 1 to 3.
[0030] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that the concentration of urea in the mixed aqueous solution described in step 2 is 0.01 g / mL. Other aspects are the same as those of specific embodiment 4.
[0031] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that the time of the hydrothermal reaction in step 2 is 12 hours to 16 hours. The rest is the same as specific embodiment 5.
[0032] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that the drying temperature in step 2 is 40° C. to 60° C. and the drying time is 2 h to 12 h. The rest is the same as specific embodiment 6.
[0033] Specific embodiment eight: This embodiment is the application of the iridium oxide / nickel iron hydroxide composite catalyst in specific embodiment one, specifically as a catalyst in a hydrogen evolution reaction.
[0034] The present invention is verified by the following tests:
[0035] Experiment 1: This experiment is a method for preparing an iridium oxide / nickel iron hydroxide composite catalyst, which is specifically carried out according to the following steps:
[0036] First, immerse the iron foam with a three-dimensional skeleton structure of 2cm×2cm×1mm in acetone for ultrasonic cleaning for 15 minutes, and then wash it with anhydrous ethanol and deionized water for multiple times, and then put the cleaned iron foam into a vacuum drying oven for drying;
[0037] 2. Turn on the dielectric barrier discharge and place it for preheating treatment. The appearance of glow discharge under normal pressure is close to blue light, which means the discharge is uniform and stable. After the preheating treatment is completed, put the fully dried iron foam between the two disc electrodes in the dielectric barrier discharge device, adjust the power to 60W, and perform discharge treatment on the iron foam for 10 minutes to obtain pretreated iron foam.
[0038] 3. Weigh 0.087 g of nickel nitrate, 0.057 g of iridium oxide, 0.3 g of urea and 0.092 g of ammonium fluoride, dissolve in 30 mL of deionized water, and stir with a magnetic stirrer at room temperature until a transparent solution is obtained; then put the metal iron foam after the plasma pretreatment in step 1 into it so that it is completely immersed, transfer them together into a polytetrafluoroethylene high-pressure reactor, place them in a forced air drying oven for hydrothermal reaction, the temperature of the hydrothermal reaction is 130° C., and the reaction time is 16 h. After naturally cooling to room temperature, take out the sample, wash it with deionized water and anhydrous ethanol for several times, and then place it in a forced air drying oven for drying, the drying temperature is 50° C., and the time is 8 h, to obtain an iridium oxide / nickel iron hydroxide composite catalyst.
[0039] Figure 1 The XRD pattern of the iridium oxide / nickel iron hydroxide composite catalyst prepared for test 1 is shown in the figure. The diffraction peaks at 27.9°, 39.9° and 65.9° correspond to the crystallographic facets of IrO2 (JCPDS No.88-0288), which match well with the (110), (200) and (112) planes, respectively. Meanwhile, some crystal planes of FeOOH (JCPDS No.81-0464), such as (110) and (112), are confirmed by the characteristic peaks appearing at 21.2° and 65.6°, respectively. The four diffraction peaks of NiFe2O4 are located at about 30.2°, 35.7°, 62.7° and 74.6°, corresponding to the (220), (311), (440) and (533) crystal planes of NiFe2O4 (JCPDS No.03-0875), respectively. This proves that the iridium oxide / nickel iron hydroxide composite catalyst was synthesized by a one-step hydrothermal method.
[0040] Figure 2 This is a high-magnification SEM image of the iridium oxide / nickel iron hydroxide composite catalyst prepared in Experiment 1. Figure 3 This is a low-magnification SEM image of the iridium oxide / nickel iron hydroxide composite catalyst prepared in experiment 1. From the image, it can be seen that the morphology of cellular iridium oxide and nickel iron oxide are uniformly grown on the plasma pretreated foam iron catalytic material.
[0041] Comparative Example: The only difference from Experiment 1 is that step 2, that is, no dielectric barrier discharge plasma pretreatment is performed, and the other conditions are the same. Finally, an iridium oxide / nickel iron hydroxide composite catalyst is obtained by forming an iron foam board without dielectric barrier discharge pretreatment.
[0042] Experiment 2: This experiment is a test of hydrogen evolution performance: a three-electrode system is used in a 1.0 M potassium hydroxide solution, with different catalysts (products of Experiment 1 and Comparative Example) as working electrodes, mercury / mercury oxide electrode as reference electrode, and graphite as counter electrode to test the hydrogen evolution performance. Figure 4This is the hydrogen evolution polarization curve in Experiment 2. ● corresponds to the catalyst prepared in Experiment 1, and ▲ corresponds to the catalyst prepared in the corresponding proportion. The figure shows that plasma pretreatment of the iron foam matrix in Experiment 1 has a significant effect on improving the catalyst performance.
[0043] Experiment 3: This experiment is a test of hydrogen evolution performance: a three-electrode system is used in a 1.0M potassium hydroxide solution, with different catalysts (the product prepared in Experiment 1, the untreated three-dimensional skeleton structure iron foam referred to as the substrate in Step 1 of Experiment 1, the iron foam substrate pretreated in Step 1 of Experiment 1, and the Pt / C / foam iron composite catalyst) as working electrodes, mercury / mercury oxide electrode as reference electrode, and graphite as counter electrode, to test the hydrogen evolution performance. Figure 5 This is the hydrogen evolution polarization curve in Experiment 3. It can be seen from the figure that the plasma pretreated foam iron substrate has significantly better hydrogen evolution performance than the untreated iron substrate, proving that plasma pretreatment has a significant effect on improving hydrogen evolution performance. It can also be seen from the figure that the overall hydrogen evolution performance of the iridium oxide / nickel iron hydroxide composite catalyst is close to that of the precious metal platinum carbon Pt / C, and the preparation cost is greatly reduced, which indicates that the iridium oxide / nickel iron hydroxide composite catalyst can be used as an efficient electrocatalytic hydrogen evolution catalyst. The preparation method of the Pt / C / foam iron composite catalyst is different from the preparation method of the Pt / C / NFelectrodes disclosed in Exceptional Performance of HierarchicalNi-FeOxyhydroxide@NiFeAlloy Nanowire Array Electrocatalysts for LargeCurrentDensityWater Splitting (DOI: 10.1039 / c9ee02388g) only in that the foam carrier is different, and the rest are the same.
Claims
1. A method for preparing an iridium oxide / nickel iron hydroxide composite catalyst, characterized in that The preparation method of the iridium oxide / nickel iron hydroxide composite catalyst is carried out according to the following steps:
1. Plasma surface pretreatment of metallic iron foam with three-dimensional skeleton structure using dielectric barrier discharge; 2. adding the metallic iron foam after the plasma pretreatment in step 1 into a mixed aqueous solution of nickel nitrate, iridium oxide, urea and ammonium fluoride to completely immerse it, and then subjecting it to a hydrothermal reaction. After the reaction is completed, the iridium oxide / nickel iron hydroxide composite catalyst is obtained by washing and drying in sequence; The mass ratio of the nickel nitrate, iridium oxide, urea and ammonium fluoride is (8-9):(5-6):(30-32):(9-10); The temperature of the hydrothermal reaction is 120°C to 140°C.
2. The method for preparing an iridium oxide / nickel iron hydroxide composite catalyst according to claim 1, characterized in that The power of the dielectric barrier discharge described in step 1 is 50W to 100W.
3. The method for preparing an iridium oxide / nickel iron hydroxide composite catalyst according to claim 2, characterized in that The dielectric barrier discharge time described in step 1 is 8 minutes to 12 minutes.
4. The method for preparing an iridium oxide / nickel iron hydroxide composite catalyst according to claim 1, characterized in that In step 1, before pretreatment, the metal iron foam with a three-dimensional skeleton structure needs to be immersed in acetone for ultrasonic cleaning, and then washed multiple times with anhydrous ethanol and deionized water respectively, and then placed in a vacuum drying oven for drying.
5. The method for preparing an iridium oxide / nickel iron hydroxide composite catalyst according to claim 1, characterized in that The concentration of urea in the mixed aqueous solution described in step 2 is 0.01 g / mL.
6. The method for preparing an iridium oxide / nickel iron hydroxide composite catalyst according to claim 1, characterized in that The hydrothermal reaction time in step 2 is 12 h to 16 h.
7. The method for preparing an iridium oxide / nickel iron hydroxide composite catalyst according to claim 1, characterized in that The drying temperature in step 2 is 40° C. to 60° C., and the drying time is 2 h to 12 h.
8. The use of an iridium oxide / nickel iron hydroxide composite catalyst as claimed in claim 1, characterized in that Iridium oxide / nickel iron hydroxide composite catalyst is used as catalyst in hydrogen evolution reaction.
Citation Information
Patent Citations
Iridium-doped ferronickel oxide-based composite catalyst as well as preparation method and application thereof
CN117089885A
Iridium monatomic oxygen-rich vacancy nickel hydroxide nanosheet as well as preparation method and application thereof
CN118256951A